“The way up is the way down”: Curzio Malaparte’s “Il Cristo Proibito” and Krzysztof Kieślowski’s “Three Colours: Red” - Coates, Paul (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The statement ‘the way up is the way down’ may imply that the spiritual way to perfection lies through humility. It may however also apply to the physical world that is the source of such spiritual metaphors, and within which the actions play out of fictional characters who themselves serve as metaphors for real ones. I will argue that both meanings apply to both of these films, with a comparison between the two films enabling one to employ Malaparte’s explicit prohibition of a Christ-like position to make apparent a similar prohibition that is only implicit in Kieślowski’s film. Such physical movements provide an appropriate topography for the concern with judgment, knowledge, revenge, isolation and humiliation embodied in the male protagonists of the two films. In each case, the protagonists’ eventual divestment from programmes of judgment and revenge may be related to the prohibition Malaparte formulates explicitly: that upon human re-enactment of the Christ-like position that is the one of judgment. Here a destructive and self-destructive movement downwards, in the sense of dehumanization and extreme isolation, is countered eventually by a downward one that, in fact, leads upwards through an embrace of the humiliation of inaction. The paper examines various ways in which the object of both texts is to rediscover a ‘we’ that is rather one of solidarity than complicity.